Rainfall frequency analysis using LH-moments approach: A case of Kemaman Station, Malaysia - Amani Zakaria, Zahrahtul; Moath Ali Suleiman, Jarah; Mohamad, Mumtazimah (International Journal of Engineering and Technology, 2018)
Statistical analysis of extreme events is often carried out to obtain the probability distribution of floods data and then predict the occurrence of floods for a significant return period. L-moments approach is known as the most popular approach in frequency analysis. This paper discusses comparison of the L-moments method with higher order moments (LH-moments) method. LH-moment, a generalization of L-moment, which is proposed based on the linear combinations of higher-order statistics has been used to characterize the upper part of distributions and larger events in flood data. It is observed from a comparative study that the results of the analysis of observed data and the diagram based on the K3D-II distribution using LH-moments method is more efficient and reasonable than the L-moments method for estimating data of the upper part of the distribution events.Â